Acute ischemic stroke versus transient ischemic attack: Differential plaque morphological features in symptomatic intracranial atherosclerotic lesions. (February 2021) - Xiao, Jiayu; Padrick, Matthew M.; Jiang, Tao; Xia, Shuang; Wu, Fang; Guo, Yu; Gonzalez, Nestor R.; Li, Shujuan; Schlick, Konrad H.; Dumitrascu, Oana M.; Maya, Marcel M.; Diniz, Marcio A.; et al.
Abstract: Background and aims: Intracranial atherosclerotic disease (ICAD) is a major etiologic cause for acute ischemic stroke (AIS) and transient ischemic attack (TIA). The study was designed to investigate if differential morphological features exist in symptomatic atherosclerotic lesions between AIS and TIA patients. Methods: The culprit plaques from 45 AIS patients and 42 TIA patients were analyzed for the degree of stenosis, vessel wall irregularity, normalized wall index (NWI), remodeling index, plaque-wall contrast ratio (CR), high signal intensity on T1-weighted images, plaque enhancement ratio and enhancement grade. These plaque features along with clinical characteristics were compared between AIS and TIA groups as well as between their stenosis degree-matched subgroups. Results: Overall, grade 2 enhancement (OR 3.85, 95%CI 1.42–10.46, p = 0.006) and hyperlipidemia (OR 3.04, 95%CI 1.13–8.22, p = 0.025) were independent indicators for AIS, whereas high NWI (OR 1.47, 95%CI 0.76–2.86, p = 0.004) was associated with TIA. In the comparison between the subgroups with moderate (30%–69%) stenosis, high plaque-wall CR (OR 5.38, 95%CI 1.39–20.75, p = 0.008) was associated with AIS, whereas high NWI (OR 2.50, 95%CI 0.61–10.00, p = 0.006) was associated with TIA. Conclusions: Our study reveals differential morphological features in symptomatic ICAD lesions between AIS and TIA patients. Probing these features with MR vessel wall imaging may provide insights into the prognosis of patients with ICAD. Graphical abstract: Image 1 Highlights: Differential plaque features were found between stroke and transient ischemic attack. Grade 2 enhancement and high plaque-wall contrast ratio were associated with stroke. High normalized wall index was associated with transient ischemic attack.